Comparison between retracked sea level and regional ocean modelling system (ROMs) - Mohamad Sufi Mohamad Pisol, 1995- , author; Nurul Hazrina Idris, supervisor; Fakulti Geoinformasi dan Harta Tanah (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Geoinformatik)) - Universiti Teknologi Malaysia, 2018